2003
DOI: 10.3353/omp.8.55
|View full text |Cite
|
Sign up to set email alerts
|

Dentigerous Cyst Associated with a Supernumerary Malformed Tooth: Report of a case and a clinicopathologic review.

Abstract: Dentigerous cyst associated with a supernumerary malformed tooth: Report of a case and a clinicopathologic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The objectives of jaw cyst resection are to terminate the pathological process, promote the restoration of jaw bone tissue, and restore the anatomical and physiological functions of the teeth in the cyst area [15,16] . According to traditional surgical methods, root canal therapy and apical resection should be adopted as long as the tooth can be retained, regardless of the pulp activities in the cystic area [4,5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objectives of jaw cyst resection are to terminate the pathological process, promote the restoration of jaw bone tissue, and restore the anatomical and physiological functions of the teeth in the cyst area [15,16] . According to traditional surgical methods, root canal therapy and apical resection should be adopted as long as the tooth can be retained, regardless of the pulp activities in the cystic area [4,5] .…”
Section: Discussionmentioning
confidence: 99%
“…It was assessed by Visual Analogue Scale (VAS) [14] . For each patient, pain was recorded as follows: mild pain (VAS, 1-2) was 16 patients (80%), and moderate pain (VAS,3-4) was four patients (20%), heavy pain (VAS, 5-6) was 0 patients (0%) [15] .…”
Section: Pain Intensitymentioning
confidence: 99%
“…But it was reported that dentigerous cysts associated with supernumerary teeth are rare. Moreover, in younger children, the report of the dentigerous cyst associated with supernumerary teeth is fewer [1][2][3][4][5] . In these cases, dentigerous cysts should be removed or be marsupialized for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Only one case reported the use of nitrous oxide with general and local anaesthesia [96]. Some of the included clinical studies did not mention the type of anaesthetic technique used [10,14,16,17,21,35,36,39,42,44,46,49,50,51,54,55,57,59,66,68,70,74,78,79,81,82,85,89,90,93,98,102,103]. In one study the extracted tooth was re-planted after the marsupialization, however there was no enough long term follow-up [16].…”
Section: Treatment Modalitymentioning
confidence: 99%